Peran Kepala Madrasah dalam Pengembangan Prestasi Non-Akademik Peserta Didik - Miranti Amri, An'nisa (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2026)
The purpose of this study is to describe the role of the madrasah principal in developing non-academic student achievement at MAN 1 Parepare City. It also explores the principal's strategies in developing non-academic student achievement at MAN 1 Parepare City. It also examines the supporting and inhibiting factors, as well as the challenges faced by the madrasah principal in developing non-academic student achievement at MAN 1 Parepare City.This study employed a qualitative approach with a descriptive approach. Data were collected through in-depth interviews with eight informants, observation, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. This study was conducted at Madrasah Aliyah Negeri (MAN) 1 Parepare City. The results indicate that 1) The role of the madrasah principal has proven effective in developing non-academic student achievement. The madrasah principal acts as a motivator, facilitator, and supervisor, actively providing moral support, direct guidance during training and competitions, facilitating student needs, and serving as a role model in mentoring both teachers and students. This role is in line with the EMASLIM leadership theory and shows that the madrasah principal is a key actor in creating a madrasah climate that supports the development of student potential. 2) The madrasah principal's strategy includes 6 strategies, namely planning, coaching, motivation, facilitation, evaluation and supervision, and collaboration. (3) Supporting factors include teacher-parent cooperation, student interest, competitive mentality, madrasah facilities, and scheduled training. Inhibiting factors include lack of interest among some students, limited funds, lack of support from some parents, and the unavailability of expert coaches for some types of competitions. The biggest challenge for the madrasah principal is managing the balance between academic and non-academic students and increasing student readiness to face increasingly fierce competition.